Green economy: problems, paths and mechanisms built to Kazakhstan (Eurasian Journal of Ecology, 2016)
The paper discusses the status and problems of the transition to sustainable development. The analysis and the necessity of immediate construction in Kazakhstan "green economy." Based on the theory and takinginto account the similar experience of advanced countries to provide direction, the ways and mechanisms of selected acceleration.
Keywords: the "green economy"; "green consumers"; "green purchasing"; "green products"; "Green Marketing and Communications"; "green building"; "green home"; "green roofs and walls"; eco-innovation and "clean technology"; "green investments"; "green agriculture"; "